2022
DOI: 10.3389/fmolb.2022.998475
|View full text |Cite
|
Sign up to set email alerts
|

ERK signaling for cell migration and invasion

Abstract: The RAS - Extracellular signal-regulated kinase (RAS-ERK) pathway plays a conserved role in promoting cell migration and invasion. Growth factors, adhesion, and oncogenes activate ERK. While historically studied with respect to its control of cell proliferation and differentiation, the signaling pattern and effectors specific for cell migration are now coming to light. New advances in pathway probes have revealed how steady-state ERK activity fluctuates within individual cells and propagates to neighboring cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 91 publications
2
29
0
Order By: Relevance
“…The result indicated that the cell migration got markedly reduced after targeted inhibition by siRNA showing that ERK may have a role on cell adhesion molecules. This is in accordance with many recent evidences (Hunter et al, 2022).Evidences from the cell invasion assay also indicated that specific ERK modulation can actually change cell invasion rate suggesting an ERK dependent ECM theory (Samson et al, 2022).…”
Section: Table 3: Values Of Parameters With Control Group With Respec...supporting
confidence: 92%
“…The result indicated that the cell migration got markedly reduced after targeted inhibition by siRNA showing that ERK may have a role on cell adhesion molecules. This is in accordance with many recent evidences (Hunter et al, 2022).Evidences from the cell invasion assay also indicated that specific ERK modulation can actually change cell invasion rate suggesting an ERK dependent ECM theory (Samson et al, 2022).…”
Section: Table 3: Values Of Parameters With Control Group With Respec...supporting
confidence: 92%
“…We also showed that ORF21 mediated the upregulation of the MEK pathway and anchorage-independent cell growth ( Figure 7 ). Although RhoA–ROCK signaling is well known to promote cell migration [ 32 , 33 ], the MEK pathway has also been reported to contribute to the promotion of cell migration [ 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…7). Although RhoA-ROCK signaling is well known to promote cell migration [32,33], the MEK pathway has also been reported to contribute to the promotion of cell migration [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%